The cumulative prevalence of termination of parental rights for U.S. children, 2000-2016 - Wildeman, Christopher (Child maltreatment, 2020)
Recent research has used synthetic cohort life tables to show that having a Child Protective Services investigation, experiencing confirmed maltreatment, and being placed in foster care are more common for American children than would be expected based on daily or annual rates for these events. In this article, we extend this literature by using synthetic cohort life tables and data from the Adoption and Foster Care Analysis and Reporting System to generate the first cumulative prevalence estimates of termination of parental rights. The results provide support for four conclusions. First, according to the 2016 estimate, 1 in 100 U.S. children will experience the termination of parental rights by age 18. Second, the risk of experiencing this event is highest in the first few years of life. Third, risks are highest for Native American and African American children. Nearly 3.0% of Native American children and around 1.5% of African American children will ever experience this event. Finally, there is dramatic variation across states in the risk of experiencing this event and in racial/ethnic inequality in this risk. Taken together, these findings suggest that parental rights termination, which involves the permanent loss of access to children for parents, is far more common than often thought.